A Scientometrics Analysis of the Research Publications in JIF Quartile Open-Access Journals of Medical Informatics - Gulam Jilani; Swapna Banerjee (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2026)
Background: Medical informatics has become an increasingly important interdisciplinary field that integrates healthcare, information technology, and data management. The rapid growth of open-access publishing has expanded the dissemination of medical informatics research, yet a comprehensive understanding of publication patterns, citation impact, collaboration networks, and emerging research themes within high-impact open-access journals remains limited.Objective: This study aims to analyze the scientific publication landscape of medical informatics research published in Journal Impact Factor (JIF) quartile-ranked open-access journals, focusing on publication growth, citation performance, influential sources, author collaboration, thematic evolution, and research trends.Methods: A scientometric approach was employed using data retrieved from the Web of Science database. Following the PRISMA screening procedure, 17,915 open-access articles published in ten JIF quartile-ranked medical informatics journals were included in the analysis. Bibliometrix/Biblioshiny, VOSviewer, and Microsoft Excel were utilized to examine publication productivity, citation impact, co-citation networks, keyword co-occurrences, funding patterns, and international collaborations.Results: The dataset comprised 17,915 publications that received 381,038 citations and demonstrated an annual growth rate of 23.62%. The Journal of Medical Internet Research emerged as the most productive and influential source, contributing 7,344 publications and receiving 214,341 citations. Keyword analysis identified mHealth, health, and care as dominant themes, while internet, impact, artificial intelligence, and COVID-19 represented emerging research topics. International collaboration was strongest between the United States and China, while the United States Department of Health and Human Services and the National Institutes of Health were the leading funding agencies.Conclusion: The findings demonstrate the substantial growth and global influence of open-access medical informatics research. The field is increasingly shaped by digital health technologies, mobile applications, artificial intelligence, and internet-based healthcare innovations. This study provides a comprehensive overview of research productivity, scholarly impact, and thematic developments, offering valuable insights for researchers, publishers, policymakers, and funding agencies in advancing medical informatics research.